下顎骨前歯部に発生した類皮囊胞の1例 - 伊藤, 邦弘; 加藤, 三香子; 瀧川, 友佳子; 近藤, さゆり; 風岡, 宜暁; 古橋, 明文 (日本口腔外科学会雑誌, 2022)
Dermoid cysts occur commonly in the soft tissues of the head and neck but seldomly in the jaw. We report a rare case of a dermoid cyst in the mandible. A 19-year-old woman was referred to our department for further evaluation of the mandible. Panoramic radiography showed a radiolucent mandibular lesion. Computed tomography revealed a cystic lesion in the anterior region of the mandible. A mandibular cyst was clinically diagnosed, prompting the complete excision of the lesion under general anesthesia. The definitive histopathological diagnosis was dermoid cyst. The patient showed no signs of recurrence one year and two months following the operation.